A multidisciplinary treatment of congenitally missing maxillary lateral incisors: a 14-year follow-up case report (Journal of Applied Oral Science, 2014)
Absence of the maxillary lateral incisor creates an aesthetic problem which can be managed in various ways. The condition requires careful treatment planning and consideration of the options and outcomes following either space closure or prosthetic replacement. Recent developments in restorative dentistry have warranted a re-evaluation of the approach to this clinical situation. Factors relating both to the patient and the teeth, including the presentation of malocclusion and the effect on the occlusion must be considered. The objective of this study was to describe the etiology, prevalence and alternative treatment modalities for dental agenesis and to present a clinical case of agenesis of the maxillary lateral incisors treated by the closure of excessive spaces and canine re-anatomization. A clinical case is presented to illustrate the interdisciplinary approach between orthodontics and restorative dentistry for improved esthetic results. In this report, the treatment of a girl with a Class II malocclusion of molars and canines with missing maxillary lateral incisors and convex facial profile is shown. Treatment was successfully achieved and included the space closure of the areas corresponding to the missing upper lateral incisors, through movement of the canines and the posterior teeth to mesial by fixed appliances as well as the canines transformation in the maxillary lateral incisors. This is a 14-year follow-up case report involving orthodontics and restorative dentistry in which pretreatment, posttreatment, and long-term follow-up records for the patient are presented.